HUBUNGAN MOTIVASI DAN MINAT BELAJAR TERHADAP HASIL BELAJAR MATEMATIKA SISWA SMA MODEL AL-KHAWARIZMI PULAU SEBUKU - Agus Syarifuddin (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2016)
The purpose of this research of mutual knowing (1) the relationship between motivation to learn the results of high school students learning mathematics model Al-Khwarizmi Sebuku Island School Year 2015/2016. (2) To examine the relationship between interest in learning the results of high school students studying Mathematics Model Al-Khwarizmi Sebuku Island School Year 2015/2016. (3) To examine the relationship between motivation and interest in learning the learning outcomes of students of Mathematics Model Al-Khwarizmi Sebuku Island School. The method used in this research is descriptive quantitative analysis. The population in this study were high school students Model Al-Khwarizmi Sebuku Island totaling 79 people, while the sample are students of class X and XI High School Model Al-Khwarizmi Sebuku Island totaling 59 people. The sampling technique used in this study is that the probability sampling random.Teknikanalisis data in this study using a simple correlation and double correlation . Teknik data collection was conducted by questionnaire and documentation. Results obtained by the questionnaire and the results of student learning Mathematics. (1) There is a positive relationship between motivation and learning outcomes of study Mathematics with a relatively high coefficient of 0,778. (2) There is a positive and significant correlation between interest in learning the results of learning mathematics students with a relatively high coefficient of 0,674. (3) Based on the results turned out to be greater than F or Ftabel 40.23> 3.16, then Ho is rejected and Ha accepted means there is a positive and significant correlation between motivation and interest in learning about the mathematics and the relationship contributed 66.3% of high school students in Al-Khwarizmi Model Sebuku Island. Keywords: Motivation And Interest Related Learning